Predicting M-Payment Adoption Intention in Indonesia: Integrating Technology Acceptance Model and Psychological Factors - Priyanto Susiloadi; Theda Renanita; Julaibib (Universitas Muhammadiyah Surakarta, 2023)
The government is currently promoting the growth of m-payment usage in Indonesia. Therefore, research is needed to identify the factors influencing the adoption intention of m-payment. One theory frequently employed to elucidate the usage intention of m-payment is the Technology Acceptance Model (TAM). According to this theory, intention arises from perceived usefulness and perceived ease of use. This study integrates TAM with psychological variables, namely, trust and subjective norms. This research aims to examine the factors influencing the adoption intention of m-payment. Before conducting the model test, this research begins with adapting and validating all measurement tools in the Indonesian language. Participants in this study are individuals aged 17 and above who own smartphones. The entire data collection is done online. The research instrument is validated with confirmatory factor analysis (CFA) on perceived usefulness, perceived ease of use, trust, subjective norm, and the adoption intention of m-payment (N=209). The model test is conducted through path analysis (N=210). The validation process confirms the theoretical model of the five instruments in the Indonesian version. The CFA results indicate that all five research instruments meet the cut-off criteria for fit indices RMSEA, CFI, TLI, and SRMR. The path analysis results reveal that perceived usefulness, perceived ease of use, and subjective norm influence the adoption intention of m-payment. In contrast, trust does not affect the adoption intention of m-payment. This research contributes both theoretically and practically, particularly regarding the factors influencing m-payment adoption.